Anti-MDA5 Antibody-positive Dermatomyositis Complicated by Autoimmune-associated Hemophagocytic Syndrome That Was Successfully Treated with Immunosuppressive Therapy and Plasmapheresis - Fujita, Yuya (Intern Med, 2018)
A 56-year-old Japanese woman with muscle weakness, increased creatine kinase and aldolase levels, and characteristic cutaneous lesions was diagnosed with anti-melanoma differentiation-associated gene 5 antibody (anti-MDA5 antibody)-positive dermatomyositis. She also had interstitial lung disease (ILD). After corticosteroid and tacrolimus combination therapy was started, bicytopenia and elevated serum ferritin and transaminase emerged. Because the bone marrow tissues were hypoplastic with hemophagocytes, she was diagnosed with concomitant autoimmune-associated hemophagocytic syndrome (HPS). Intravenous cyclophosphamide pulse therapy and plasmapheresis were performed. The laboratory findings indicated improved abnormalities, and the ILD did not progress. Anti-MDA5 antibody-positive dermatomyositis can be complicated by HPS.